Health Risk Assessment of Heavy Metals in Green Mussel (Perna viridis) and Oyster (Magallana bilineata) harvested in Northern Luzon, Philippines - Cleah D. Benitez, Kathlene; Almagro, Allysa Ross; Jalyn S. Baldoza, Bernajocele; Bryan S. Perelonia, Karl; E. Tanyag, Bryan; Jann M. Quiambao, Jerick; M. Montojo, Ulysses (Journal of Marine and Coastal Science, 2025)
Bivalves are a significant global food source due to their affordability, abundance, and nutritional value. However, urbanization and tourism introduce pollutants like heavy metals particularly cadmium (Cd), lead (Pb), and mercury (Hg), raising public health concerns. Bivalve samples are collected using convenience sampling during dry and wet seasons. Environmental water samples are also collected for comparative assessment of heavy metals. Using Graphite Furnace–Atomic Absorption Spectroscopy, heavy metal concentrations in edible tissues of bivalves were analyzed. Health risk assessments, including Lifetime Average Daily Dose (LADD), Hazard Quotient (HQ), and Carcinogenic Risk (CR), were evaluated following U.S. EPA and FAO/WHO. For green mussels the Cd levels averages to 0.0071 mg/kg for both seasons. On the other hand, Cd levels of oyster averages to 0.0298 mg/kg. Both bivalves show Pb and Hg concentrations less than the method detection limits of 0.0480 and 0.0173 mg/kg, respectively. These concentrations were within regulatory limits of Cd, Pb, and Hg set by EU Regulation 2023/915, i.e., 1, 1.5, and 0.5 mg/kg, respectively. LADD did not exceed the Provisional Tolerable Daily Intake, while HQ and CR values were below the threshold value of one, indicating no associated health risks. Hence the study can be used to formulate risk management measures and public health advisories. Furthermore, the study excluded other bivalve and univalve species endemic to the growing areas which highlights the need for risk assessment monitoring to ensure food safety.